On *Soft Turing Point with Separation Axioms (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
" In this paper, we use the concept of the soft turing point and join it with separation axioms in soft topological space and investigate the relationship between them and  study the most important properties and  results of it.